ARCHITECTURAL SOLUTIONS OF NATIONAL STYLE HOTELS IN HISTORIC CITIES - Saidkhonova Umida Ziyodullayevna; Arziyev Dilshod Amriddinovich; Shaumarova Dilnoza Abduhabirovna (Galaxy International Interdisciplinary Research Journal, 2022)
At a time when economic conditions are changing, the adaptation and conversion of historical structures is an increasingly popular approach. Some historic buildings are very suitable for the restoration of modern hotels. The article analyzes the relationship between the hotel, the city and its architectural heritage, as well as some of the factors that led to the emergence of alternative hotel models through a number of successful solutions. Many problems of hotel design in historic buildings are listed and appropriate solutions are suggested. Some methodological guidelines are outlined, and specific guidelines and principles have been developed for further action in this area. In summary, their practical application is discussed and some shortcomings and limitations are listed.